The Clout of Lifestyle on Students’ Consumptive Behavior - Ratna, Istika; Yusuf, Budi Permana (Edueksos Jurnal Pendidikan Sosial & Ekonomi, 2024)
The consumptive behavior among teenagers continues to increase due to excessive lifestyle following trends for self-existence. This study desires to find out the influence of lifestyle on consumptive behavior and the magnitude of this influence. It uses quantitative research methods and a population of students from senior high schools  in Kalisari, East Jakarta. Random sampling was used in this study with the sample used was 122 respondents. The data collection techniques used in this study are observation and questionnaires. The data analysis technique used was simple linear regression. The analysis results of the research are the significance obtained from the results of hypothesis testing, which is 0.000 meaning, calculate> t table (5.111 > 1.979) and significance 0.000 < 0.05 so that Ho is rejected, Ha is accepted, this means that lifestyle positively influences consumptive behavior in the students of senior high schools  in Kalisari, East Jakarta. Lifestyle affects consumptive behavior in senior high schools  in Kalisari, East Jakarta students by 17.9%, including the deficient category. Consumptive behavior can only be avoided with awareness from oneself, who feels the need not to do consumptive behavior.Keywords: Lifestyle, students, consumptive behavior